Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Tujuan dan Fungsi Al-Quran di MAN 3 Parigi - Muhamad Latif (Jurnal Pendidikan Madrasah, 2021)
This study aims to find out the learning outcomes of class X MIA IA learners on the subjects of the Qur'an Hadith before and after using the discovery learning model. This study uses the Class action method. The research subject is a student of class X MIA 1A MAN 3 Parigi Semester I of the 2021-2022 School Year. The results showed that learning by applying discovery learning methods had a positive impact in improving learners' learning achievement which was characterized by an increase in learning completion in each cycle, namely cycle I increased by 70%, an increase quite significantly in cycle II by 86%. Thus the discovery learning model can be applied to students at the Madrasah Aliyah level to improve their learning outcomes.